2021
DOI: 10.3389/fpsyt.2021.703481
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Alzheimer's Disease and Other Dementias

Abstract: Introduction: Numerous countries went into lockdown to contain the COVID-19 outbreak, which has impeded follow-up of chronic diseases, such as cognitive impairment (CI). Cognitive and neuropsychiatric changes during the COVID-19 pandemic are neglected in China, which is the world's whistleblower. To investigate the cognitive and neuropsychologic changes in CI, as well as the proportions of rapid cognitive decline (RCD) before and during the COVID-19 pandemic to provide clinical evidence for CI intervention dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Sleep quality was measured online with the Insomnia Severity Index (ISI) ( 24 ). Cognitive assessment was performed with the Mini-Mental State Examination (MMSE) ( 10 , 11 , 13 , 19 , 20 ). Montreal Cognitive Assessment – MoCA ( 11 , 29 ), and Clinical Dementia Rating Scale (CDR) ( 9 , 11 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep quality was measured online with the Insomnia Severity Index (ISI) ( 24 ). Cognitive assessment was performed with the Mini-Mental State Examination (MMSE) ( 10 , 11 , 13 , 19 , 20 ). Montreal Cognitive Assessment – MoCA ( 11 , 29 ), and Clinical Dementia Rating Scale (CDR) ( 9 , 11 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Montreal Cognitive Assessment – MoCA ( 11 , 29 ), and Clinical Dementia Rating Scale (CDR) ( 9 , 11 , 18 ). Neuropsychiatric symptoms were assessed with the Neuropsychiatric Inventory (NPI) ( 9 , 11 , 14 , 17 , 20 ). Functionality was assessed with the Functional Assessment Questionnaire (FAQ) ( 10 ) and Basic Activities of Daily Living (ABVD) ( 10 , 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults suffering from cognitive impairment and/or neurodegenerative disorders, few studies support this hypothesis. For instance, Gan et al [ 8 ] reported in 205 patients with cognitive impairment or Alzheimer's disease, a greater decline in several cognitive scales assessed during the pandemic compared with a control group which was assessed before the pandemic. This result is consistent with the study by Tsapanou et al [ 9 ] conducted among 204 family caregivers of older adults with mild cognitive impairment or dementia who reported a significant overall decline in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…This has been observed in a recent survey of 339 Greek carers of PWD: cognitive decline was reported in patients, especially in those with moderate-to-severe dementia, together with an increase in carers’ burden ( 21 ). Gan et al ( 22 ) found signs of significant objective decline in several screening measures of global cognitive status, behavioural symptoms and daily-living activities in a sample of 205 older people with and without cognitive impairment assessed before and after enforcement of lockdown in China. A study that investigated the pre- vs. post-lockdown cognitive changes in patients with mild cognitive impairment and dementia due to Alzheimer’s disease found significant decline especially in verbal long-term memory and phonemic fluency ( 23 ).…”
Section: Introductionmentioning
confidence: 99%